2015
DOI: 10.1111/1365-2435.12577
|View full text |Cite
|
Sign up to set email alerts
|

Functional replacement across species pools of vertebrate scavengers separated at a continental scale maintains an ecosystem function

Abstract: 1. The composition of species pools can vary in space and time. While many studies are focused on understanding which factors influence the make-up of species pools, the question to which degree biogeographic variation in species composition propagates to biogeographic variation in ecological function is rarely examined. If different local species assemblages operate in ways that maintain specific ecological processes across continents, they can be regarded as functionally equivalent. Alternatively, variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…For example, mud crabs Scylla serrata are abundant, and avid scavengers of carrion, in estuaries over the austral summer (Webley 2008). The availability of carrion to estuarine scavengers might also vary as a function of seasonality, or with changes in the extent of shoreline modification (Huijbers et al 2016). Large accumulations of animal carcasses were not observed in any of the estuaries we studied, which suggests that substantial differences in carrion availability were not a major factor in contributing to observed patterns in scavenging function.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…For example, mud crabs Scylla serrata are abundant, and avid scavengers of carrion, in estuaries over the austral summer (Webley 2008). The availability of carrion to estuarine scavengers might also vary as a function of seasonality, or with changes in the extent of shoreline modification (Huijbers et al 2016). Large accumulations of animal carcasses were not observed in any of the estuaries we studied, which suggests that substantial differences in carrion availability were not a major factor in contributing to observed patterns in scavenging function.…”
Section: Discussionmentioning
confidence: 77%
“…capitalising on the regular supply of food and abundance of shelter in human modified landscapes (Aronson et al 2014, Dafforn et al 2015, Firth et al 2016, Bishop et al 2017. Species that perform important ecological processes, and which are also capable of exploiting resources in urban settings might, therefore, be important in sustaining ecological functions in disturbed ecosystems (Hobbs et al 2006, Huijbers et al 2016, Mayer-Pinto et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a number of other species that are opportunistic scavengers in estuaries are likely to be less abundant, target more specified types of prey/carrion or have smaller body sizes, thus potentially being out‐competed by species such as yellowfin bream. It has recently been suggested that high species dominance might be a common feature of scavenger assemblages (Inger, Per, Cox, & Gaston, ), and the function of carrion consumption appears to be contingent on a small number of common, and opportunistic, trophic generalists across a range of ecosystems, including forests, deserts and coastal dunes (DeVault et al, ; Huijbers et al, ; Mateo‐Tomás, Olea, Moleón, Selva, & Sánchez‐Zapata, ). In addition to being characteristics of successful scavengers, the behavioural traits (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…, Huijbers et al. ). The redistribution of energy by vertebrate scavengers, as opposed to invertebrates and decomposers, could be far more influential in ecosystem‐wide trophic interactions than is currently understood (DeVault et al.…”
Section: Introductionmentioning
confidence: 99%